2016
DOI: 10.1103/physrevlett.116.257601
|View full text |Cite
|
Sign up to set email alerts
|

Local Electrical Imaging of Tetragonal Domains and Field-Induced Ferroelectric Twin Walls in ConductingSrTiO3

Abstract: We demonstrate electrical mapping of tetragonal domains and electric field-induced twin walls in SrTiO 3 as a function of temperature and gate bias utilizing the conducting LaAlO 3 =SrTiO 3 interface and low-temperature scanning electron microscopy. Conducting twin walls appear below 105 K, and new twin patterns are observed after thermal cycling through the transition or on electric field gating. The nature of the twin walls is confirmed by calculating their intersection angles for different substrate orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 38 publications
6
45
1
Order By: Relevance
“…Even more recently Ma et al . 23 used low temperature scanning electron microscopy and electron beam induced current for the investigation of LAO/STO structures. They not only demonstrated that highly conducting filaments exist but they also showed that these filaments may be surrounded by insulating areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more recently Ma et al . 23 used low temperature scanning electron microscopy and electron beam induced current for the investigation of LAO/STO structures. They not only demonstrated that highly conducting filaments exist but they also showed that these filaments may be surrounded by insulating areas.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no restoring force this may require a long time and temperatures elevated well above the phase transition temperature as also observed by Ma et al . 23 . In our case an almost complete redistribution only seems to occur above 180 K which may indicate a thermal activation.…”
Section: Discussionmentioning
confidence: 99%
“…To explore this route, however, one first needs to understand whether (and how) the ferroelastic degrees of freedom can be harnessed via a suitable external field. As the ferroelastic domain walls have recently been shown to be polar [16][17][18][19][20][21][22], it is reasonable to expect that they will respond to an electrical bias. A detailed study on the evolution of the domain wall topology upon application of a voltage is currently missing, leaving the above question largely unanswered.…”
Section: Low-temperature Dielectric Anisotropy Driven By An Antiferromentioning
confidence: 99%
“…A very likely scenario is that they act as trapping centres for the photo-generated oxygen vacancies (or photo-mobilized oxygen vacancies which migrate from the bulk to the surface) which give rise to the itinerant electrons. The pinning of the oxygen vacancies may be caused by the local strain and, as was mentioned already in the introduction, by a polar charging of the domain boundaries due to a so-called flexoelectric effect [21][22][23]. The formation of oxygen vacancy clusters may also play an important role since it can give rise to a further reduction of the Coulomb-interaction with the itinerant electrons and thus enhance the lifetime of the photogenerated charge carriers.…”
Section: Iiib) Photo Doping Of Sto (110)mentioning
confidence: 99%
“…For example, room temperature ferroelectricity has been observed in STO thin films that are grown under tensile strain on top of a DyScO 3 substrate [20]. Moreover, a polar order that is likely induced by a flexoelectric effect has been observed in the vicinity of the domain boundaries of the structural poly-domain state that appears below T* [21][22][23][24][25] and can even modify the …”
mentioning
confidence: 99%